Processing and characterization of atz and ysz-graphene composites for fabrication of mems scale microthruster - Markandan, Kalaimani (2017)
Structural ceramics such as zirconia and alumina are widely used in the materials industry owing to their high hardness, chemical inertness and electrical insulation properties. However, they bear the disadvantage of low fracture toughness that has limited their further applications. As such, ceramics with improved fracture toughness are desired in many engineering fields.